2018
DOI: 10.1007/s10517-018-4087-9
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Cholinergic Abnormalities in Mnestic Processes with Diterpene Alkaloid Songorine

Abstract: Repeated administration of songorine to mice restored mnestic processes impaired by scopolamine treatment, which manifested in improvement of CPAR conditioning and normalization of behavioral activity throughtout the observation period. This thearpeutical effect surpassed that of pyracetam used as the reference drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Such possible dopaminergic action of SON in addition to its presently reported GABA(A)-receptor agonist effect seems to be reasonable from the perspective of our present behavioral findings and earlier data [ 12 , 13 ]. In line with an earlier experiment of Nesterova et al (2015) [ 12 ], the animals in the present EOM experiment showed a marked decrease of anxiety-like behavior after the administration of SON similar to the GABA(A) receptor positive allosteric modulator DZP but without the signs of locomotor disturbances that are typical in the case of benzodiazepine derivatives [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such possible dopaminergic action of SON in addition to its presently reported GABA(A)-receptor agonist effect seems to be reasonable from the perspective of our present behavioral findings and earlier data [ 12 , 13 ]. In line with an earlier experiment of Nesterova et al (2015) [ 12 ], the animals in the present EOM experiment showed a marked decrease of anxiety-like behavior after the administration of SON similar to the GABA(A) receptor positive allosteric modulator DZP but without the signs of locomotor disturbances that are typical in the case of benzodiazepine derivatives [ 23 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pharmacokinetic studies have confirmed that systemically applied SON rapidly distributes in body tissues, and passes the blood–brain barrier resulting in a well-detectable level of the drug in the CNS [ 10 , 11 ]. Regarding the effects of SON on higher-order CNS functions, only sparse data are available so far which suggest the potential anxiolytic and even procognitive action of SON in laboratory mice [ 12 , 13 ] However, only a few studies have investigated the psychopharmacological targets of SON, and the findings are not yet coherent. An earlier in vitro study suggested that SON may act as a putative gamma-aminobutyric acid (GABA) receptor A antagonist based on electrophysiological recordings in hippocampal slices of young rats [ 14 ] without any in vivo evidence for the similar action of SON.…”
Section: Introductionmentioning
confidence: 99%
“…[11 -17] Among them, songorine, an atisine type diterpene alkaloid exerts acetylcholinesterase (AChE) inhibitory effects. [18] In order to seek compounds with unique structures and strong activities, investigation on the roots of A. leucostomum Worosch. has been carried out, resulting the isolation of two new diterpenoid alkaloids, leucostosine C (1), a novel C 18 -diterpenoid alkaloid having the 7-amino group, and leucostosine D (2), together with six known ones (3 -8) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, about fifty diterpenoid alkaloids have been isolated from this plant [11–17] . Among them, songorine, an atisine type diterpene alkaloid exerts acetylcholinesterase (AChE) inhibitory effects [18] . In order to seek compounds with unique structures and strong activities, investigation on the roots of A. leucostomum Worosch.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic studies confirmed that systemically applied SON rapidly distributes in body tissues, and passes the blood-brain barrier resulting in a welldetectable level of the drug in the CNS [10,11]. Regarding the effects of SON on higherorder CNS functions, only sparse data are available so far which suggest the potential anxiolytic and even procognitive action of SON in laboratory mice [12,13] However, only a few studies investigated the psychopharmacological targets of SON, and the findings are not yet coherent. An earlier in vitro study suggested that SON may act as a putative gamma-aminobutyric acid (GABA) receptor A antagonist based on electrophysiological recordings in hippocampal slices of young rats [14] without any in vivo evidence for the similar action of SON.…”
Section: Introductionmentioning
confidence: 99%